2007
DOI: 10.1080/10976640701545073
|View full text |Cite
|
Sign up to set email alerts
|

Operator Induced Variability in Left Ventricular Measurements with Cardiovascular Magnetic Resonance is Improved After Training

Abstract: An intensive two month training period significantly improved the accuracy of LV functional measurements. Adequate training of new CMR operators is of paramount importance in our aim to maintain the accuracy and high reproducibility of CMR in LV function analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
94
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 24 publications
3
94
0
Order By: Relevance
“…22 The BOLD analysis has been previously published. 18 Briefly, myocardial signal intensity was measured after manually tracing the endocardial and epicardial contours using QMass version 6.2.3 software (Medis Medical Quantification Software).…”
Section: Cmr Data Analysismentioning
confidence: 99%
“…22 The BOLD analysis has been previously published. 18 Briefly, myocardial signal intensity was measured after manually tracing the endocardial and epicardial contours using QMass version 6.2.3 software (Medis Medical Quantification Software).…”
Section: Cmr Data Analysismentioning
confidence: 99%
“…This observed deterioration of the interobserver agreement is most likely related to the fact that no precise rules for adjusting the contours were predefined and that the observers were not specially trained in the tracing of plaque contours. Previous work has shown that training and adherence to predefined rules substantially improves the interobserver agreement of data analysis based on contour tracing [15,16]. Previous studies have evaluated the reproducibility of plaque quantification using the currently analyzed software [3,9,17].…”
mentioning
confidence: 99%
“…2,3,5 Cardiovascular magnetic resonance allows accurate, noninvasive assessment of left ventricular structure and function in humans. 6 Computational atlas formation has also introduced the possibility of capturing 3-dimensional geometric variation within populations to explore risk factor influences. 7,8 We used these techniques to reveal for the first time the impact of preterm birth on left ventricular structure and function in humans.…”
mentioning
confidence: 99%